2020
DOI: 10.1111/ina.12751
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of SARS‐CoV‐2 by inhalation of respiratory aerosol in the Skagit Valley Chorale superspreading event

Abstract: During the 2020 COVID-19 pandemic, an outbreak occurred following attendance of a symptomatic index case at a regular weekly rehearsal on 10 March of the Skagit Valley Chorale (SVC). After that rehearsal, 53 members of the SVC among 61 in attendance were confirmed or strongly suspected to have contracted COVID-19 and two died. Transmission by the airborne route is likely. It is vital to identify features of cases such as this so as to better understand the factors that promote superspreading events. Based on a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
774
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 619 publications
(843 citation statements)
references
References 74 publications
15
774
1
5
Order By: Relevance
“…The epidemiological data of this analysis showed that 10 subjects seated in three neighboring tables were infected, although the video record showed no close contact or fomite contact. Another analysis 4 of a superspreading event of COVID‐19 in a choral rehearsal confirms the likability of this airborne transmission mode. In this event, 53 members out of 61 confirmed or strongly suspected to have contracted COVID‐19.…”
Section: Introductionmentioning
confidence: 55%
“…The epidemiological data of this analysis showed that 10 subjects seated in three neighboring tables were infected, although the video record showed no close contact or fomite contact. Another analysis 4 of a superspreading event of COVID‐19 in a choral rehearsal confirms the likability of this airborne transmission mode. In this event, 53 members out of 61 confirmed or strongly suspected to have contracted COVID‐19.…”
Section: Introductionmentioning
confidence: 55%
“…However, "despite consistent evidence as to SARS-CoV-2 contamination of surfaces and the survival of the virus on certain surfaces, there are no specific reports which have directly demonstrated fomite transmission" (World Health Organization, 2020). This contrasts with the airborne transmission, documented as the only possible route in many superspreading events (Miller et al, 2020;Shen et al, 2020).…”
Section: How Is Sars-cov-2 Transmitted?mentioning
confidence: 88%
“…The main mode of transmission during the SSE is considered to be inhalation of droplet aerosols. The important factors established were closed rooms with ventilation running, long hours of being together in a single room and the presence of a single person spreading substantial amounts of virus [30].…”
Section: Discussionmentioning
confidence: 99%